Prevalence of chewing side preference in the deciduous, mixed and permanent dentitions - Barcellos, Daphne Camara [UNESP]; de Paiva Gonçalves, Sergio Eduardo [UNESP]; da Silva, Melissa Aline [UNESP]; Batista, Graziela Ribeiro [UNESP]; Pleffken, Patricia Rondon [UNESP]; Pucci, César Rogério [UNESP]; Borges, Alessandra Buhler [UNESP]; Torres, Carlos Rocha Gomes [UNESP] (Jaypee Brothers Medical Publishing, 2011)
Aim: This study evaluated the prevalence of the chewing side preference (CSP) in the deciduous, mixed and permanent dentitions. Materials and methods: Three-hundred subjects were divided in three groups (n = 100): Group 1 - children with deciduous dentition; group 2-children with mixed dentition; group 3 - subjects with permanent dentition. The CSP was determined using a direct method (visual observation) developed by McDonnell et al. (2004). Descriptive statistic was used to observe the prevalence of CSP. The Pearson's Chi-square was used to investigate signicant associations between gender, presence of CSP and preferred side (right/left). Results and conclusion: Eighty-seven percent of group 1 had a CSP. Eighty-two percent of group 2 had a CSP. Seventy-six percent of group 3 had a CSP. There was no statistically significant association between presence of CSP and gender in all groups. There was no statistically significant association between preferred side (right/left) and gender in all groups. Clinical significance: There is a higher prevalence of subjects in deciduous, mixed and permanent dentition that presented chewing side preference. The early diagnosis of the presence of chewing side preference can prevent the unilateral chewing pattern with prophylactic therapy applied to the first teeth (deciduous).
Keywords: Chewing side preference; Deciduous dentition; Mastication; Mixed dentition; Permanent dentition; adolescent; adult; chewing gum; child; dentition; female; hemispheric dominance; human; male; mastication; middle aged; physiology; preschool child; sex difference; Adolescent; Adult; Chewing Gum; Child; Child, Preschool; Dentition, Mixed; Dentition, Permanent; Dentition, Primary; Female; Functional Laterality; Humans; Male; Middle Aged; Sex Factors; Young Adult